Concept And Term Relationship in The Domain of Gender Terminology - Azimova Nilufar Nuriddinovna; Mulladjanova Nasiba Azimdjanovna (Genius Journals, 2022)
The article considers the term gender as one of the most important categories in the social life of mankind, based on which the concepts of "woman" and "man" are studied. The gender expression of linguoculturalism in proverbs and works of art in Uzbek and English was also discussed. In particular, on the basis of the linguoculture "happiness" it is studied that different views on the happiness of men and women are reflected in the works in Uzbek and English
Keywords: Cognitive Linguistics; Concept; Genealogy; Literary Translation.